Integrated Hierarchical Cobalt Sulfide/Nickel Selenide Hybrid Nanosheets as an Efficient Three-dimensional Electrode for Electrochemical and Photoelectrochemical Water Splitting - Hou, Yang; Qiu, Ming; Nam, Gyutae; Kim, Min Gyu; Zhang, Tao; Liu, Kejun; Zhuang, Xiaodong; Cho, Jaephil; Yuan, Chris; Feng, Xinliang (Nano Letters, 2017)
Developing highly active electrocatalysts for photoelectrochemical water splitting is critical to bring solar/electrical-to-hydrogen energy conversion processes into reality. Herein, we report a three-dimensional (3D) hybrid electrocatalyst that is constructed through in situ anchoring of Co9S8 nanosheets onto the surface of Ni3Se2 nanosheets vertically aligned on an electrochemically exfoliated graphene foil. Benefiting from the synergistic effects between Ni3Se2 and Co9S8, the highly conductive graphene support, and large surface area, the novel 3D hybrid electrode delivers superior electrocatalytic activity toward water reduction in alkaline media, featuring overpotentials of -0.17 and -0.23 V to achieve current densities of 20 and 50 mA cm-2, respectively, demonstrating an electrocatalytic performance on the top of the Ni3Se2- and Co9S8-based electrocatalysts as reported in literature. Experimental investigations and theoretical calculations confirm that the remarkable activity of the obtained material results from the unique 3D hierarchical architecture and interface reconstruction between Ni3Se2 and Co9S8 through Ni-S bonding, which leads to charge redistribution and thus lowers the energy barrier of hydrogen desorption in the water splitting process. Further integration of the 3D hybrid electrode with a macroporous silicon photocathode enables highly active and sustainable sunlight-driven water splitting in both basic media and real river water. The overall water splitting with 10 mA cm-2 at a low voltage of 1.62 V is achieved using our hybrid as both anode and cathode catalysts, which surpasses that of the Ir/C-Pt/C couple (1.60 V) for sufficiently high overpotentials.
CRIS-Team Scopus Importer:2023-03-20
Keywords: earth-abundant hybrid catalyst; electrocatalysis; photoelectrocatalysis; strong coupling effect; Three-dimensional hierarchical architecture; water splitting